Facial dermatoses in patients with blepharitis: A cross-sectional prospective analysis - GUDER, SEMİH; Guder, Semih; ÇULFA, ŞAFAK; Çulfa, Şafak (My University, 2022)
Introduction: The relationship between facial dermatoses and blepharitis has been known for a long time. Objectives: We aimed to investigate the frequency of accompanying facial dermatoses in patients with blepharitis and their relationship with the severity of blepharitis. Methods: In this cross-sectional study, 95 patients with blepharitis were examined for attending facial dermatoses. The type of blepharitis, the severity of blepharitis, and the degree of dry eye were determined in the patients. Dermoscopic and microscopic examinations were used in the diagnosis of facial dermatoses. The history of allergic rhinitis was questioned because Demodex species frequently accompany blepharitis, facial dermatoses, and allergic rhinitis patients. Mann-Whitney U test was used compare 2 independent groups. In comparing categorical variables, Pearson chi-Squared, Fishere Exact, and Fisher-Freeman-Holton tests were used. Results: At least 1 facial dermatosis was detected in 84.2% patients, and we did not see any facial dermatosis in 15.8% ones. No patients had acne, which is one of the most common facial dermatoses. The most common facial dermatosis detected in our patients was facial demodicosis (57.9%). It was followed by seborrheic dermatitis (22.1%) and rosacea (12.6%), respectively. In addition, 2.1% of the patients had atopic eyelid dermatitis, 23.2% had a history of allergic rhinitis, and 63.2% had ocular demodicosis. Conclusions: It is essential to perform dermatological examinations of all patients with blepharitis in terms of accompanying facial dermatoses and their early diagnosis.
Keywords: Blepharitis; demodicosis; facial dermatoses; rosacea; seborrheic dermatitis